Centrosome function is critical during terminal erythroid differentiation - Tátrai, P; Gergely, F (EMBO Press, 2022)
Red blood cells are produced by terminal erythroid differentiation, which involves the dramatic morphological transformation of erythroblasts into enucleated reticulocytes. Microtubules are important for enucleation, but it is not known if the centrosome, a key microtubule-organizing center, is required as well. Mice lacking the conserved centrosome component, CDK5RAP2, are likely to have defective erythroid differentiation because they develop macrocytic anemia. Here, we show that fetal liver-derived, CDK5RAP2-deficient erythroid progenitors generate fewer and larger reticulocytes, hence recapitulating features of macrocytic anemia. In erythroblasts, but not in embryonic fibroblasts, loss of CDK5RAP2 or pharmacological depletion of centrosomes leads to highly aberrant spindle morphologies. Consistent with such cells exiting mitosis without chromosome segregation, tetraploidy is frequent in late-stage erythroblasts, thereby giving rise to fewer but larger reticulocytes than normal. Our results define a critical role for CDK5RAP2 and centrosomes in spindle formation specifically during blood production. We propose that disruption of centrosome and spindle function could contribute to the emergence of macrocytic anemias, for instance, due to nutritional deficiency or exposure to chemotherapy.